An experimental study of the solubility and speciation of thorium in chloride-bearing aqueous solutions at temperatures up to 250 °C. (15th October 2018) - Nisbet, H.; Migdisov, A.; Xu, H.; Guo, X.; van Hinsberg, V.; Williams-Jones, A.E.; Boukhalfa, H.; Roback, R.
Abstract: The solubility and speciation of Th in Cl-bearing solutions saturated in ThO2 was investigated experimentally at 150, 175, 200, 225 and 250 °C, and saturated water vapor pressure. At these experimental conditions (pH25°C  < 3.8, mNaCl < 2.5), Th-chloride complexation is insignificant, and the solubility of Th is controlled by hydrolysis. The two main species in solution were identified as Th(OH)2 2+ and Th(OH)4 ° and formed via the reactions T h 4 + + 2 O H - ↔ T h ( O H ) 2 2 + and T h 4 + + 4 O H - ↔ T h ( O H ) 4 0 . The logarithms of the formation constants determined for the first reaction are 23.91 ± 0.05, 24.79 ± 0.07, 25.78 ± 0.05, and 25.85 ± 0.05 for 175, 200, 225 and 250 °C, respectively, and 42.18 ± 0.06, 43.50 ± 0.07, 43.17 ± 0.08, and 43.74 ± 0.11 for the second reaction at the same temperatures. Formation constants could not be determined reliably for 150 °C. Extrapolations of our formation constants to 25 °C are in excellent agreement with the values determined at 25 °C by Neck and Kim (2001) and Ekberg et al. (2000). For natural systems buffered by thorianite (ThO2 ), the solubility determined in our study likely reflects a minimum, as the presence of additional ligands would lead to higher solubility.